2005
DOI: 10.1152/ajpregu.00492.2004
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous warming promotes sleep onset

Abstract: Sleep occurs in close relation to changes in body temperature. Both the monophasic sleep period in humans and the polyphasic sleep periods in rodents tend to be initiated when core body temperature is declining. This decline is mainly due to an increase in skin blood flow and consequently skin warming and heat loss. We have proposed that these intrinsically occurring changes in core and skin temperatures could modulate neuronal activity in sleep-regulating brain areas (Van Someren EJW, Chronobiol Int 17: 313-5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
139
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(151 citation statements)
references
References 46 publications
10
139
2
Order By: Relevance
“…Such changes in the Ts promote sleep onset because sleep onset latency did not show any significant difference in the present study. Such changes in the Ts at sleep onset were similar to those in previous studies in which distal skin warming promoted sleep onset in a cool environment (Kräuchi et al 2000), while proximal skin warming reduced sleep onset in the absence of postural changes and when the lights were switched off (Raymann et al 2005). The Ts of the leg and thigh, i.e., not distal but the lower extremity, increased considerably before and after the lights were switched off under all three conditions used here.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Such changes in the Ts promote sleep onset because sleep onset latency did not show any significant difference in the present study. Such changes in the Ts at sleep onset were similar to those in previous studies in which distal skin warming promoted sleep onset in a cool environment (Kräuchi et al 2000), while proximal skin warming reduced sleep onset in the absence of postural changes and when the lights were switched off (Raymann et al 2005). The Ts of the leg and thigh, i.e., not distal but the lower extremity, increased considerably before and after the lights were switched off under all three conditions used here.…”
Section: Discussionsupporting
confidence: 88%
“…A possible mechanism in humans involves skin warming, which has been shown to increase neuronal activity in the POAH that comprises areas critically involved in both sleep and arousal regulation (Van Someren 2004, 2006Egan et al 2005;Raymann and Van Someren 2007). Such a mechanism is also supported by recent reports that subtle skin warming accelerates sleep onset in young healthy adults, despite being less comfortable (Raymann et al 2005). In the present study, there was an increase in the Ts of the thigh, leg, foot, and chest Body-mass loss (gm -2 h -1 ) Fig.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, our results are in general accordance with findings in other suprasellar or hypothalamic diseases ( Table 5). The decrease in proximal skin temperature that we observed might explain the alterations in sleep quality and daytime wakefulness reported previously (3), as decreased proximal skin temperature is related to an increased sleep latency in both narcoleptics and healthy persons (27,28), and to sleep depth (29).…”
Section: Discussionsupporting
confidence: 70%
“…Admittedly, this association does not prove causality because patient selection may also be involved. Moreover, studies in healthy subjects showed that a circadian increase in body temperature was actually associated with skin vasoconstriction [22]. In addition to physiological rhythms, there also appears to be a circadian pattern in the risk of death in dialysis patients.…”
Section: Circadian Patternsmentioning
confidence: 99%